Many-body effects and non-local charge fluctuations in the double perovskite Sr2FeMoO6 - Martins, Henrique P. (2018)
We studied the electronic structure of Sr2FeMoO6using core level and valence band photoemission. Thespectra were obtained using high energy X-rays of 1840 eV, which provide bulk sensitive information onthe electronic structure. The experimental data were analyzed using the spectral weight from clustermodel calculations. The ground state reveals a large Fe–O and Mo–O hybridization, as well as theimportance of non-local Fe–O–Mo chargefluctuations. The latter is crucial to explain the half-metalliccharacter attributed to the Sr2FeMoO6compound. The core level and valence band photoemissionspectra show charge transfer satellites. These satellites are related to many-body effects and are largerfor the Fe levels than for the Mo states.